A Randomized Controlled Trial of the Efficacy and Safety of CCX282-B, an Orally-Administered Blocker of Chemokine Receptor CCR9, for Patients with Crohn’s Disease - Keshav, Satish (Public Library of Science, 2013)
CCX282-B, also called vercirnon, is a specific, orally-administered chemokine receptor CCR9 antagonist that regulates migration and activation of inflammatory cells in the intestine. This randomized, placebo-controlled trial was conducted to evaluate the safety and efficacy of CCX282-B in 436 patients with Crohn’s disease. Crohn’s Disease Activity Index (CDAI) scores were 250–450 and C-reactive protein >7.5 mg/L at study entry. In addition to stable concomitant Crohn’s medication (85% of subjects), subjects received placebo or CCX282-B (250 mg once daily, 250 mg twice daily, or 500 mg once daily) for 12 weeks. They then received 250 mg CCX282-B twice daily, open-label, through week 16. Subjects who had a clinical response (a ≥70 point drop in CDAI) at week 16 were randomly assigned to groups given placebo or CCX282-B (250 mg, twice daily) for 36 weeks. Primary endpoints were clinical response at Week 8 and sustained clinical response at Week 52. During the 12-week Induction period, the clinical response was highest in the group given 500 mg CCX282-B once daily. Response rates at week 8 were 49% in the placebo group, 52% in the group given CCX282-B 250 mg once daily (odds ratio [OR] = 1.12; p = .667 vs placebo), 48% in the group given CCX282-B 250 mg twice daily (OR = 0.95; p = .833), and 60% in the group given CCX282-B 500 mg once daily (OR = 1.53; p = .111). At week 12, response rates were 47%, 56% (OR = 1.44; p = .168), 49% (OR = 1.07; p = .792), and 61% (OR = 1.74; p = .039), respectively. At the end of the Maintenance period (week 52), 47% of subjects on CCX282-B were in remission, compared to 31% on placebo (OR = 2.01; p = .012); 46% showed sustained clinical responses, compared to 42% on placebo (OR = 1.14; p = .629). CCX282-B was well tolerated. Encouraging results from this clinical trial led to initiation of Phase 3 clinical trials in Crohn’s disease.